Nurse-led interventions to manage hypertension in general practice: A systematic review protocol. Issue 3 (June 2020) - Chowdhury, Sudipta; Stephen, Catherine; McInnes, Susan; Halcomb, Elizabeth
Abstract: Aim: This systematic review seeks to synthesise randomised controlled trials reporting the impact of interventions delivered by nurses in primary care to enhance blood pressure control and minimise lifestyle risk factors in hypertensive patients. Background: Given the growing demand for chronic care management, there has been a rapid increase in the primary care nursing workforce and emerging diversity in their roles. The primary care nurse's role has evolved to work in collaboration with general practitioners to manage patients with chronic conditions like hypertension. Despite the nurse's role in lifestyle modification and behaviour change, there is limited evidence exploring the impact of primary care nurse-initiated interventions for lifestyle modification in those with hypertension. Design/methods: A systematic review of randomised controlled trials will be conducted. Electronic databases will be searched from January 2000 to January 2019, using a structured search strategy. Two reviewers will review title and abstract, screen full-text papers and extract data. The Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) will be used to appraise study quality. Data will be synthesised using either meta-analysis or narrative synthesis depending on the heterogeneity of included studies. Discussion: This review will assist in understanding the evidence available on the impact of general practice nurse interventions to manage hypertension. The findings will assist in informing effective nurse-directed interventions for controlling hypertension and will identify gaps in the literature for future research to address.